Clinical diagnosis and treatment of pediatric-onset relapsing polychondritis with airway involvement - Wang, Ying; Xie, Zhibo; Chen, Jiarui; Li, Xiaoyan (Frontiers in Pediatrics, 2025)
ObjectiveWe herein retrospectively analyzed the clinical characteristics and treatment protocols of children with relapsing polychondritis (RP) with airway involvement.MethodsWe reviewed the medical records of eight children with pediatric-onset RP with airway involvement who presented to Shanghai Children's Hospital from June 2021 to June 2024. All children met Damiani's criteria for the diagnosis of RP. One child underwent “laryngotracheal reconstruction with hyoid graft + T-tube implantation + bioabsorbable corticosteroid-eluting stent implantation,” while five children underwent “balloon dilatation + T-tube implantation + bioabsorbable corticosteroid-eluting stent implantation.” After the initial surgery, follow-up was performed every two months for a total of six months. Three bioabsorbable corticosteroid-eluting stents were placed in the upper left and upper and lower right T-tubes during this time.ResultsAll eight children were seen in our department for outpatient follow-up: one child was extubated; five children remained in outpatient follow-up; and the remaining two children continued to be treated in the rheumatology and immunology department due to poor control of their primary disease.ConclusionTracheotomy can be used to rapidly improve symptoms of dyspnea in children with RP disease progression. In the stable stage of the disease, the minimally invasive surgical method of “balloon dilatation + T-tube implantation + bioabsorbable corticosteroid-eluting stent implantation” was adopted to reduce secondary injury caused by surgical trauma (to the extent possible) and to improve the survival and quality of life of the children.